2022
DOI: 10.3389/fcvm.2022.964977
|View full text |Cite|
|
Sign up to set email alerts
|

Effective management of atherosclerosis progress and hyperlipidemia with nattokinase: A clinical study with 1,062 participants

Abstract: Nattokinase (NK), known as a potent fibrinolytic and antithrombotic agent, has been shown to have antiatherosclerotic and lipid-lowering effects. However, data on human clinical studies are limited. In this clinical study involving 1,062 participants, our objective was to examine the efficacy of NK in atherosclerosis and hyperlipidemia and safety at the dose of 10,800 FU/day after 12 months of oral administration. Various factors, including lower doses that influence NK pharmacological actions, were also inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…We also found HDL-C and TG benefits in the combined supplementation, which was not significant in a recent study using the same supplementation for 4 months ( 33 ); likewise, study participants were CAD patients in our study whereas the previous trial by Liu et al recruited patients diagnosed with dyslipidemia but not CAD, therefore may have different physiological effects after the intervention. In studies with NK alone, another small pilot study by Wu et al used a higher nattokinase dosage (4,000 Fu) but in a relatively short trial period (8 weeks) did not observe significant changes in lipid markers ( 34 ), and Chen et al found improved lipid profile only with 10,800 FU/d regimen but not 3,600 FU/d in a 12-month trial among patients who were hyperlipidemic ( 35 ). These findings together suggest that using a robust dose supplementation regimen could potentially introduce significant effects on more markers over a prolonged period, while when NK and RYR are combined, the effective dosage is lower and requires a shorter time length than using them separately.…”
Section: Discussionmentioning
confidence: 99%
“…We also found HDL-C and TG benefits in the combined supplementation, which was not significant in a recent study using the same supplementation for 4 months ( 33 ); likewise, study participants were CAD patients in our study whereas the previous trial by Liu et al recruited patients diagnosed with dyslipidemia but not CAD, therefore may have different physiological effects after the intervention. In studies with NK alone, another small pilot study by Wu et al used a higher nattokinase dosage (4,000 Fu) but in a relatively short trial period (8 weeks) did not observe significant changes in lipid markers ( 34 ), and Chen et al found improved lipid profile only with 10,800 FU/d regimen but not 3,600 FU/d in a 12-month trial among patients who were hyperlipidemic ( 35 ). These findings together suggest that using a robust dose supplementation regimen could potentially introduce significant effects on more markers over a prolonged period, while when NK and RYR are combined, the effective dosage is lower and requires a shorter time length than using them separately.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Adding SFRP5 to the existing risk prediction model could improve MACE prediction in patients with CAD. Hyperlipidemia is widely acknowledged as an independent risk factor for coronary atherosclerosis, contributing to the increased complexity and severity of coronary artery lesions and thereby significantly affecting patient prognosis [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that natto intake is inversely correlated with cardiovascular disease mortality in Japanese adults 14 . In addition, nattokinase, the primary active enzyme in natto, has been shown to inhibit the progression of atherosclerosis 15 . Thus, it is unequivocal that natto has anti-atherosclerotic effects.…”
Section: Discussionmentioning
confidence: 99%